2017
DOI: 10.5897/ajb2017.16157
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase and polyphenol oxidase activities associated to somatic embryogenesis potential in an elite hybrid genotype of Theobroma cacao L.

Abstract: Cross-fertilization and somatic embryogenesis stand as potential useful tools for genetic improvement and vulgarization of agronomical interesting cocoa planting material for sustainable cocoa culture. Manual cross-fertilization (♀SNK13×♂UPA143) was conducted. ♀SNK13×♂UPA143 derived hybrid genotypes were tested for their susceptibility to black pods disease (BPD). The most tolerant hybrid genotype (KHACa12) was monitored for its precocity, yielding and somatic embryo potential. Peroxidase and polyphenol oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This shows that the lowest concentrations are sometimes insufficient to overcome the recalcitrant ; however, when they are too high they cause toxicity regardless of the compound. Inhibition of somatic embryo production of T. cacao would be due, in addition to the insufficiency or toxicity of certain compounds used, to a strong secretion of ethylene and polyphenols by the explants of certain genotypes according to Fang et al (2014) and Minyaka et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the lowest concentrations are sometimes insufficient to overcome the recalcitrant ; however, when they are too high they cause toxicity regardless of the compound. Inhibition of somatic embryo production of T. cacao would be due, in addition to the insufficiency or toxicity of certain compounds used, to a strong secretion of ethylene and polyphenols by the explants of certain genotypes according to Fang et al (2014) and Minyaka et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Alemanno et al (1996) and Boutchouang et al (2016) conducted on cacao flowers showed that they would synthesize a significant quantity of phenolic compounds. Indeed, these compounds intervene in the defense of plants (Kouassi et al, 2017a;Minyaka et al, 2017). When the plant is subjected to mechanical injury, simple phenols are synthesized and the peroxidase activity characteristic of the lignifying tissues is stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…showing that tolerance to brown pod rot was under genetic control and could be improved; explaining that the presence of susceptible and resistant genotypes in the same hybrid family confirms an excellent combination of parental genes (Cilas et al, 2004;Manga et al, 2016;Effa et al, 2017;Minyaka et al, 2017;Ondobo et al, 2017). and Ficup 34 showed necrotic surfaces greater than 0.5 cm 2 and more, none of the hybrid genotypes reached a necrosis area of 1 cm 2 (Table 2).…”
Section: Foliar Disk Infection Testmentioning
confidence: 96%